Simulation study on cadastral control infrastructure project by licensed surveyors - 371937 Muhammad Nasri Yahaya (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2008